Plagiarism Awareness and Academic Writing Ability: The Relationship with the EFL Students' Plagiarism Practice - Maulidya Namira; Maria Ping; Bibit Suhatmady (Faculty of Teacher Training and Education, Mulawarman University, 2021)
Plagiarism is considered as the writing difficulty and has been a topic among researchers in the past ten years. Many studies explored plagiarism perceptions and the reasons behind plagiarism. Some studies also attempted to find an association between the elements that might contribute to plagiarism such as writing skills, language level, studying behavior, etc. However, most of the studies does not include the plagiarism rate or similarity index as one of the research variables. To fill this gap, this study aimed to find out whether there is any relationship between plagiarism awareness and academic writing ability towards the students’ actual plagiarism practice. The 30 respondents are students of the English Department in Mulawarman University who has written an academic paper namely a Mini research proposal. This study design is quantitative-correlational design with a Multiple regression data analysis technique. The study three main findings are; (1) there is no significant relationship between plagiarism awareness and plagiarism rate; (2) there is a significant negative relationship between academic writing ability and plagiarism rate; and (3) there is a simultaneous relationship between plagiarism awareness and academic writing ability with plagiarism rate. Additionally, academic writing ability has more influence on plagiarism rate than plagiarism awareness.